A Community Survey of Referral Sources to Identify Primary Care and Gender-Affirming Care Providers - Anja Jokela, MD; Maija Reblin, PhD (Elsevier, 2024)
Introduction: Barriers exist in access to primary care as well as specialty healthcare such as gender-affirming care. Understanding the referral sources used to identify new providers for these types of care can help healthcare systems facilitate access. Methods: Using data from a community-based survey, demographics and information relevant to finding new healthcare providers were assessed. Results: Data from 165 participants suggest that seeking a new primary care provider was perceived as challenging. The most common referral sources for primary care providers were family/friends, a doctor, or a medical center website. The most common referral sources for gender-affirming care providers were a doctor, family/friends, or social media. There were significant differences in the types of referral sources most likely to be utilized for primary versus gender-affirming care. Conclusions: Personal connections, including trusted doctors, can be important sources of provider referrals. Additional resources may be needed to facilitate their ability to make quality connections. Community resources and social media can be important sources when existing social networks may not have knowledge about the needs of particular communities, especially those who may be at risk of discrimination. More inclusive and secure referral sources may be needed to ensure gender-affirming care referrals are made.